Haemophilia A: Mutation Type Determines Risk of Inhibitor Formation - Schwaab, R; Brackmann, H-H; Meyer, C; Seehafer, J; Kirchgesser, M; Haack, A; Olek, K; Tuddenham, E G D; Oldenburg, J (Thrombosis and Haemostasis, 1995)
The formation of factor VIII antibodies is a major problem for replacement therapy of haemophilia A patients. Antibodies occur in 5-30% of patients with severe haemophilia A. The reason for antibody formation is still unknown. In this study we correlate for the first time different factor VIII gene mutations, stop- and missense mutations, large and small deletions and intrachromosomal intron 22 recombinations to antibody formation. A total of 364 patients with known inhibitor status of our institute, of the database, and of 3 studies representing intron-22-inversion data are included. The results show that the risk for developing factor VIII antibodies is strongly related to stop mutations, large deletions and intrachromosomal recombinations. A probable explanation could be the complete lack of endogenous circulating factor VIII protein in these cases. Other factors that might be important for the pathogenesis of inhibitor formation, e. g. the antenatal period, as well as possible therapeutic effects, are discussed.